Tectonometamorphic evolution of Medium-P granulites of the Namaqua Metamorphic Province at the Gordonia Subprovince marginal zone, southern Namibia - Sebetlela, Teboho (Department of Geological Sciences, 2017)
The western Namaqua Metamorphic Complex (NMC) is a Mesoproterozoic mediumto low-pressure, high temperature metamorphic belt that is characterised by a complex, polyphase Mesoproterozoic metamorphic history. Using an integrated approach, the P-T-t evolution of a portion of the marginal zone between two major tectonic domains in the western NMC: the Richtersveld and Gordonia Subprovices is investigated, with the aim of resolving a P-T-t path for the peak to retrograde evolution of a major regional thrust, that will in turn help to elucidate its geodynamic significance. The Kum Kum Klippe represents a structural outlier of the Gordonia Subprovince, located at the frontal zone of the Grunau Terrane, where the Grunau Terrane (hangingwall), Pella Terrane (footwall) and the bounding Lower Fish River Thrust Zone (LFRTZ) are all well exposed. The Pella Terrane in this region shows signi ficant lithological heterogeneity and is constituted by felsic orthogneisses, metama fic rocks and leucogranite intrusives, while the Grunau Terrane is dominated by pelitic granulites. The LFRTZ along the southwestern margin of the Kum Kum Klippe is a ~30-40 m wide tabular zone primarily localised in the Pella Terrane. Phase equilibria modelling of pelitic granulites from the hangingwall constrains peak metamorphic P-T conditions of ~5.2-5.9 kbar and ~790-815°C which are correlated to a monazite growth event at c. 1262-1184 Ma. Sheared pelitic granulites constrain the P-T conditions for early stage shearing in the LFRTZ to ~2.8-5.0 kbar and ~640-785°C which likely occurred shortly after peak metamorphism. Pella amphibolite samples from the footwall and LFRTZ constrain the conditions of tectonic juxtaposition to ~2.7 kbar and ~542°C which must have occurred subsequent to cooling from suprasolidus conditions and is thus constrained at <1184 Ma. The constrained peak to retrograde P-T-t path is characterised by a short segment of substantial decompression subsequent to peak metamorphic conditions at c. 1262-1184 Ma. This is followed by a period dominated by cooling with only a small component of concomitant decompression, which together with the early decompressive segment likely correspond to the period of retrograde shearing, which ultimately led to tectonic juxtaposition in the mid-amphibolite facies at c. <1184 Ma. The P-T path presented suggests that the LFRTZ does not represent a terrane bounadry that juxtasposes crustal entities which converged and collided as the result of Wilson cycle subduction to collision tectonics. Contrastingly the metamorphism at highly elevated geotherms and largely cooling dominated retrograde trajectory determined in this study are more compatible with a continental backarc setting, which has recently been proposed as an alternative model. Thus the P-T constraints presented in this study contradict the collisional model and terrane concept that has long been widely accepted for the western NMC.